Directional preference in dogs: Laterality and "pull of the north" - Adámková, Jana; Svoboda, Jan; Benediktová, Kateřina; Martini, Sabine; Nováková, Petra; Tůma, David; Kučerová, Michaela; Divišová, Michaela; Begall, Sabine; Hart, Vlastimil; Burda, Hynek (PloS one, 2017)
Laterality is a well described phenomenon in domestic dogs. It was shown that dogs, under calm Earth's magnetic field conditions, when marking their home ranges, tend to head about north- or southwards and display thus magnetic alignment. The question arises whether magnetic alignment might be affected or even compromised by laterality and vice versa. We tested the preference of dogs to choose between two dishes with snacks that were placed left and right, in different compass directions (north and east, east and south, south and west or west and north) in front of them. Some dogs were right-lateral, some left-lateral but most of them were ambilateral. There was a preference for the dish placed north compared to the one placed east of the dog ("pull of the north"). This effect was highly significant in small and medium-sized breeds but not in larger breeds, highly significant in females, in older dogs, in lateralized dogs but less significant or not significant in males, younger dogs, or ambilateral dogs. Laterality and "pull of the north" are phenomena which should be considered in diverse tasks and behavioral tests with which dogs or other animals might be confronted. The interaction and possible conflict between lateralization and "pull of the north" might be also considered as a reason for shifted magnetic alignment observed in different animal species in different contexts.
Keywords: Behavior, Animal; Dogs; mužské pohlaví; ženské pohlaví; změna polohy v prostoru; Magnetic Fields; zvířata; Orientation, Spatial; Functional Laterality; psi; Female; Male; funkční lateralita; chování zvířat; magnetické pole; Animals